Effect of Financial Performance on Share Price on Listed Companies In Indonesia Stock Exchange - Suhendro, Handayani, R. Riana Dewi & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aimed to determine the effect of market value, profitability,solvency, activity and liquidity to the stock price on the companysconsumer goods manufacturing industry sectors listed on the IndonesiaStock Exchange. The independent variable in this study is the Price EarningRatio (PER), Return on Equity (ROE), Debt to Equity Ratio (DER), TotalAssets Turnover (TATO), the Current Ratio (CR) and Return on Assets(ROA). While the dependent variable in this study is the stock price.Sampling was done by using purposive sampling method. The sample usedin this study is a company manufacturing consumer goods industry sectorlisted in Indonesia Stock Exchange in the period 2014-2016, with a total of23 companies. The results of this study concluded that the variable return onequity and total asset turnover affect the stock prices of companiesmanufacturing consumer goods industry sector, while the variable PriceEarning Ratio, Debt to Equity Ratio, Current Ratio, and return on assetsdoes not affect the stock prices of companies manufacturing consumergoods industry sector.Keywords: Financial Performance, Stock Price